Characterization of an N‐glycosylated Bacillus subtilis leucine aminopeptidase expressed in Pichia pastoris. (11th November 2014) - Xi, Hongxing; Tian, Yaping; Zhou, Nandi; Zhou, Zhemin; Shen, Wei
<x xml:space="preserve">Abstract</x> Aminopeptidase is an important flavorsome especially in protein hydrolysate debittering by removing hydrophobic amino acid residue at the N‐terminal end. Besides, it is also applied to preparation of active peptides and analysis of protein sequence. In this study, leucine aminopeptidase from Bacillus subtilis was cloned and expressed in Pichia pastoris, a widely used heterologous protein expression host. Then it was purified and characterized. After methanol induction for 96 h, the aminopeptidase activity in culture supernatant reached 28.4 U ml−1, which was 7.1 times that of wild strain B. subtilis Zj016. The optimal temperature and pH of the purified recombinant enzyme were 60 °C and 8.5, respectively. The purified aminopeptidase was stable within 30–60 °C and pH 8.0–9.0. It was intensively inhibited by Ni2+, Ca2+, DL‐dithiothreitol (DTT) and ethylene diamine tetraacetic acid (EDTA), but activated by Co2+. The Km toward leucine‐p‐nitroanilines (Leu‐pNA) of the enzyme was 0.97 mM. The sequence analysis of aminopeptidase indicated three potential N‐glycosylation sites and it was further verified via MALDI‐TOF‐MS analysis. Consequently, the N‐glycosylated aminopeptidase exhibited higher thermostability and catalytic efficiency. The purified enzyme exhibited two bands through sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS–PAGE) while a single band can be identified when the enzyme was deglycosylated. Circular dichroism spectroscopy indicated that the secondary structure of recombinant aminopeptidase was similar to the wild‐type.